The Effects of Banking Competition on Growth and Financial Stability: Evidence from the National Banking Era - Carlson, Mark; Correia, Sergio; Luck, Stephan (Journal of Political Economy, 2022)
How does banking competition affect credit provision and growth? How does it affect financial stability? In order to identify the causal effects of banking competition, we exploit a discontinuity in bank capital requirements during the nineteenth-century National Banking Era. We show that banks operating in markets with lower entry barriers extend more credit. The resulting credit expansion, in turn, is associated with additional real economic activity. However, banks in markets with lower entry barriers also take more risk and are more likely to default. Thus, we provide causal evidence that banking competition can cause both growth and financial instability.